... in den vnbeweglichen vnd vnuerruckten Fußstapffen Frühneuzeitliche Karfreitagsprozessionen als Projekt der Gegenreformation und katholischen Erneuerung - Drnovšek, Jaša (ZRC SAZU, Založba ZRC, 2020)
How can we explain the large number of Good Friday processions that characterised Catholic Europe from the 16th to the 18th century? Jaša Drnovšek presents these early modern performances as eminently political phenomena that could only exist against the background of the Counter-Reformation and Catholic renewal. In doing so, he takes up Joachim Küpper's theory of cultural production, according to which culture can be seen as a virtual network. In his comparative cultural-historical study, Drnovšek takes an in-depth look at the history of the Capuchin and Jesuit orders, both of which contributed significantly to the rise of Good Friday processions. The Škofjeloški pasijon, the oldest Slovenian drama, whose revived performance tradition has been under UNESCO protection since 2016, plays here a special role.